Seed borne Alternaria species: A review - Rathod, Sulochana (Current Botany, 2012)
Species of Alternaria cause range of diseases with great economic importance on large variety of commercially cultivated tropical crop plants which include cereals, legumes, oil seeds and large number of post harvest crops. Alternaria species causing early blight disease to the plants are known to cause wild spread damage in tropical crops.